Modelos e métodos de otimização para apoio à tomada de decisão no planejamento agrícola da cultura de laranja - Tavares, Cassiano (2025)
The 2024/25 Brazilian orange harvest is already considered the smallest in the past 30 years. This is due to a 25% drop in orchard production in the state of São Paulo and other factors such as the spread of phytosanitary diseases, a shortage of rainfall (31% lower than expected for the period), a reduction in fruit size, and a decrease in the rate of mature fruit drop. This entire scenario has led to a rise in fruit prices and a slowdown in global orange juice consumption. As a result, Brazil’s position as the world’s largest producer of oranges and orange juice since 1980 could be shaken in the medium term if no solutions are found to support strategic decisions, such as planting orange trees to meet the demands of previously signed international contracts. To face these challenges, this thesis proposes an innovative mathematical model to formally support the optimization of strategic planning for orange planting, taking into account specific characteristics of this crop, such as varietal balance in production and the control of plant age groups. The operational requirements were defined in partnership with one of the world’s largest orange juice producers and validated through computational experiments using instances based on real data. The computational results revealed several advantages of using the proposed model to support decision-making, further indicating that annual production could increase by an average of 50.59% from the ninth year until the end of the planning horizon, while meeting the company’s essential and desirable requirements. However, significant difficulty was observed in obtaining optimal solutions of the proposed model due to the complexity and scale of the real-world problem. To reduce response time, matheuristics were explored, offering reasonable solutions. Moreover, to handle conflicting objectives that arise in practice, Multiobjective Optimization techniques were applied. With these advances, this work provides practical and strategic solutions for Brazilian producers to face adversities and maintain competitiveness in the global market.